(untitled) (Bangladesh Journal of Agricultural Research, 2013)
A field trail was carried out at South-Surma, Sylhet, in 2009-10 and at FSRD site Jalalpur, Sylhet in 2010-11 in collaboration with WRC and OFRD, BARI to examine the response of 7 wheat varieties at two levels of lime in split-plot design where lime was applied in main plots and different wheat varieties were grown in sub-plots. The seeds were sown on 05 December 2009 and 30 November 2010 for the growing season of 2009-10 and 2010-11, respectively. The wheat varieties used in this study were Shatabdi, Sufi, Sourav, Bijoy, Prodip, BARI Gom-25 and BARI Gom-26. The index of relative performance of each variety in comparison to mean yield of all varieties under the contrast conditions of liming and non-liming was estimated to determine relative adaptability of wheat variety under experimental soil conditions. The result indicated that most of the yield components viz., spikes/m2, 100-grain weight, and grain yield of wheat were significantly improved by liming for both the years and locations. There were variations in lime response among the wheat varieties. The index of relative adaptability (IRA %) for yield of BARI Gom-26 and Bijoy was more than 100% for both the years. The results indicated that these two wheat varieties are relatively tolerant to low pH and could be adapted in acidic soil of Sylhet. Bangladesh J. Agril. Res. 38(1): 97-104, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15194